1983
DOI: 10.1037/0003-066x.38.9.971
|View full text |Cite
|
Sign up to set email alerts
|

Gender and social influence: A social psychological analysis.

Abstract: The impact of gender on social influence has been only incompletely understood by social scientists, although the study of social influence is one of the classic fields of social psychological inquiry. It will be argued in this article that a relation between gender and social influence has been documented in the research literature on sex differences as well as in the literature on stereotypes about male and female behavior. Studies of both types have pointed to greater influence by men and greater influencea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
219
3
9

Year Published

1984
1984
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 364 publications
(244 citation statements)
references
References 68 publications
13
219
3
9
Order By: Relevance
“…In relation to homemaker and employee roles, for example, one may wonder whether girls are socialized to acquire communal traits and boys to acquire agentic traits, with the result that women as a group are more suited to perceivers' concept of the homemaker role and men as a group to perceivers' concept of the employee role. Although we believe that socializing agents tend to prepare girls and boys for the social roles that they believe these girls and boys will probably occupy as adults (Eagly, 1983), our theory of stereotypes does' not address these issues of how people are prepared for roles and recruited into them. According to our framework, the proximal cause of gender stereotypes is the differing distributions of women and men into social roles, whatever the causation that lies behind these differing distributions.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to homemaker and employee roles, for example, one may wonder whether girls are socialized to acquire communal traits and boys to acquire agentic traits, with the result that women as a group are more suited to perceivers' concept of the homemaker role and men as a group to perceivers' concept of the employee role. Although we believe that socializing agents tend to prepare girls and boys for the social roles that they believe these girls and boys will probably occupy as adults (Eagly, 1983), our theory of stereotypes does' not address these issues of how people are prepared for roles and recruited into them. According to our framework, the proximal cause of gender stereotypes is the differing distributions of women and men into social roles, whatever the causation that lies behind these differing distributions.…”
Section: Resultsmentioning
confidence: 99%
“…Later in life, status issues further perpetuate the early socialization differences in the value of work conducted by men and women. Women and men are distributed differently into social roles; men tend to occupy higher status roles, and women occupy lower status roles (Eagly, 1983(Eagly, , 1987Eagly & Steffen, 1984). Female-typed occupations generally have had less prestige, less power, and less pay than male-typed occupations (Dexter, 1985).…”
Section: Gender and Compensationmentioning
confidence: 99%
“…To complement the understanding of gender differences in aggression, future studies also should examine gender differences in the use of indirect types of aggression (Bjorkqvist, Osterman, & Kaukiainen, 1992). Deaux (1984) and Eagly (1983) have also argued that natural settings typically offer more behavioral choices than do laboratory settings. Consequently, the results from experimental studies of aggression may reflect aggressiveness that is found only when other behavioral choices are unavailable.…”
mentioning
confidence: 99%